Assessment of economic risks in Ukrainian enterprises: Management aspect - Оksana Nuzhna; Natalia Tluchkevych; Tetyana Pisarenko (Економічний форум)
The article is devoted to practical aspects of quantitative assessment of the degree of risk in relative terms as an important component of risk management. The purpose of the research is to conduct a quantitative assessment of the degree of risk of economic activity at Ukrainian enterprises in general and with a distribution by size, based on the comparison of the obtained results to identify the most attractive for investment types of activity from the point of view of the lowest level of risk. The expediency of using a statistical method based on the extrapolation method for the quantitative assessment of the risk level is based on the study of sustainable economic development trends recorded in the past and the assumption that these trends will be preserved in the future. The ratio of the amount of losses to the total value of the property (summary of the balance sheet) of the enterprises was taken as the level of risk in relative terms. Thus, in fact, an assessment of the probability of losses at enterprises of various types of activity was carried out, which made it possible to compare the level of risk in various industries and spheres of activity and guide investors in making decisions about potentially attractive types of economic activity. It was found that the most attractive for investing funds due to the absence of loss-making enterprises in 2021 are large enterprises of such types of economic activities as temporary accommodation and catering, financial and insurance activities, real estate transactions, as well as professional, scientific and technical activities. It has been established that the highest level of risk in terms of enterprise size is observed for the following types of activities: arts, sports, entertainment and recreation (for all enterprises), supply of electricity, gas, steam and air conditioning, and mining and quarrying (for medium-sized enterprises), education (for small businesses). This is largely due to the impact of the coronavirus pandemic in 2021. It should be noted that a reliable assessment of risks in the conditions of war requires further research and analysis taking into account new political and economic factors of influence